An improved configuration for simultaneous electrochemical ESR studies: a tubular electrode in a cylindrical cavity - Wain, A; Thompson, M; Klymenko, O; Compton, R (2004)
An improved configuration for simultaneous electrochemical ESR is described in which a tubular flow cell occupies a cylindrical TE011 ESR cavity. The minimisation of dielectric loss allowed good cavity Q-values to be achieved, resulting in a high level of sensitivity and allowing good quality spectra to be attained for the N,N,N′, N′-tetramethyl-para- phenylenediamine (TMPD) radical cation and the 1,2,4,5-tetrachlorobenzoquinone (para-chloranil) and nitrobenzene radical anions. The theory describing the convective and diffusive mass transport in the tubular arrangement, along with its influence on the steady state ESR signal intensity for these stable radicals is fully developed and shown to be in good agreement with experimental results. The transient ESR response is also considered and shown to agree well with the theory presented in the literature at flow rates for which the Lévêque approximation holds.